(untitled) (Review of Knowledge Economy, 2015)
Photovoltaic effect is the emergence of a voltage between electrodes attached to a solid or liquid system up on shining light on to this system. Conjugated polymer is a molecular entity whose structure is represented as a system of alternating single and double bonds which give rise to their semi-conductor properties. Conjugated polymers are used for photovoltaic devices because, Intrinsically stable up on photoexcitation with visible light, High absorption cross-section for photon harvesting, Tunable band gap with in the entire visible spectral range and High yield of charge generation when mixed with electron acceptor materials. The important physical process in the energy conversion process that take place in polymers for photovoltaic cells are; Absorption of a photon of light by photoactive material and generation of excitons, diffusion of excitons in conjugated polymers, dissociation of charge carriers (electron-hole pair) at the donor-acceptor interface in to free carriers, transport of free carriers towards the electrodes, and extraction of the charge carriers at the respective electrode interfaces. The efficiency of converting solar to electrical energy by a solar cell depends on the band gap of the light absorbing semiconductor. Band gap (Eg) is the difference in energy between the HOMO and LUMO and there by the maximum amount of energy required for an excitation or is the energy difference between the edges of the conduction band and valence band. The power conversion efficiency is a function of band gap. For device architectures of conjugated polymer based photovoltaic cells; there are three types Single layer photovoltaic cell, Bilayer hetero junction photovoltaic cell and Bulk hetero junction Photovoltaic cell.